About the Mongolian “ОNE” word - D, Battogtokh (Mongolian Language and Literature Studies, 2024)
Recently, linguistic research has advanced new level, leading to the emergence of specialized fields such as cognitive linguistics, psycholinguistics, sociolinguistics, applied linguistics, language-culture studies, language-customs studies, and language-ethnicity studies. Additionally, focused research on specific linguistic phenomena, such as word conversion, is being conducted. In this article, we selected the basic number "one" and explored its relevance across various branches of Mongolian linguistics. We uncovered a wealth of knowledge and complex concepts through the lens of cognitive linguistics, addressing aspects such as etymology, vocabulary, symbology, and meaning. Our study also examined the term's connections to ethics, composition, usage, culture, ethnicity, and customs. Монгол хэлний “нэг” хэмээх үгийн тухай Ганц үг гээд ганцдахгүй. Дан ганц нэг үгийн судалгааг сүүлийн үед манай хэл шинжлэлчид сонирхон судалж байна. Нэг үгийн судалгааг эрдэмтэн Н.Нансалмаа “цогц ойлголт”, “цогц мэдлэг”-тэй холбон тайлбарласан бол эрдэмтэн Д.Бадамдорж танихуйн хэл шинжлэлийн цөм салбар бол танин мэдэхүйн утга зүй юм гээд мэдлэгээр илрэх танихуйн цогц ойлголтыг “багц мэдлэг” хэмээн үзжээ. Хэдийгээр нэг үг боловч түүний судалгааг хэлний бүтэц, хэл зүй, үгийн гарал зүй, утга зүй, найруулга зүй, хэрэглээний хэл зүй зэрэгтэй холбон судалбал багц мэдлэг, цогц ойлголт бүрнээ гарч, тухайн үгийн агуулгын багтаамж хүрээ, бүхэллэг утга, ухагдахууны илэрхийлэл, үг хэлээр илрэх хүний сэтгэлгээний олон талт байдал бүрнээ танигдах юм.